Analisis Yuridis Penegakan Hukum terhadap Pemalsuan Alas Hak dalam Penerbitan Sertifikat Hak Guna Usaha - fitra amalia; Saipuddin Zahri; Ismail Petanesse (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study analyzes criminal and administrative law enforcement against the forgery of land entitlement titles in the issuance of Cultivation Rights (HGU) certificates. Using a normative juridical method, it is found that criminal law enforcement relies on Articles 263, 264 and 266 of the Criminal Code, but prosecution rights are extinguished by law if the defendant dies under Article 77 of the Criminal Code. Administratively, HGU certificates issued based on forged titles are categorized as having juridical defects. The cancellation mechanism is executed by the Ministry of ATR/BPN under PP No. 18 of 2021 and Permen ATR/BPN No. 21 of 2020 without time limits if proven by a final criminal court decision.